2020
DOI: 10.1001/jama.2020.1585
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical Characteristics of 138 Hospitalized Patients With 2019 Novel Coronavirus–Infected Pneumonia in Wuhan, China

Abstract: Background: An outbreak of pneumonia associated with the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) emerged in Wuhan city and then to other city. It is very urgent to delineate the epidemiological and clinical characteristics of these affected patients. Methods: To investigate the epidemiological characteristics of the COVID-19, we describe a case series of 459 patients with con rmed COVID-19 in WZ of China from January 27 to February 12, 2020. Results: The median age of all patients was 48.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1,524
23,001
299
1,340

Year Published

2020
2020
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21,342 publications
(27,191 citation statements)
references
References 16 publications
1,524
23,001
299
1,340
Order By: Relevance
“…In addition, severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV), two notable strains of the coronavirus family, are both known to be responsible for severe complications during pregnancy, including the need for endotracheal intubation, admission to an intensive care unit (ICU), renal failure and death 7,8 . In general, both studies reported that the clinical characteristics of the pregnant women with COVID-19 pneumonia were similar to those of non-pregnant adult patients who developed COVID-19 pneumonia [2][3][4] . Chen et al 9 reported the clinical characteristics of nine pregnant women with laboratory-confirmed COVID-19 in the third trimester, which comprised mainly fever and cough.…”
Section: Clinical Manifestation Of Covid-19 Infection During Pregnancymentioning
confidence: 99%
“…In addition, severe acute respiratory syndrome coronavirus (SARS-CoV) and Middle East respiratory syndrome coronavirus (MERS-CoV), two notable strains of the coronavirus family, are both known to be responsible for severe complications during pregnancy, including the need for endotracheal intubation, admission to an intensive care unit (ICU), renal failure and death 7,8 . In general, both studies reported that the clinical characteristics of the pregnant women with COVID-19 pneumonia were similar to those of non-pregnant adult patients who developed COVID-19 pneumonia [2][3][4] . Chen et al 9 reported the clinical characteristics of nine pregnant women with laboratory-confirmed COVID-19 in the third trimester, which comprised mainly fever and cough.…”
Section: Clinical Manifestation Of Covid-19 Infection During Pregnancymentioning
confidence: 99%
“…As of 23 rd February 2020, 26 cases (16 imported and 10 indigenous) of COVID-19 had been diagnosed in Taiwan [2]. Notably, hospital-associated transmission of the COVID-19 to health-care workers and hospitalized patients has been reported [3]. Furthermore, Zou et al revealed that similar viral loads are seen in asymptomatic and symptomatic patients, indicating the transmission potential of asymptomatic patients [4].…”
Section: Effective Strategies To Prevent Coronavirus Disease-2019 (Comentioning
confidence: 99%
“…The outbreak of an epidemical pneumonia with initially unknown reasons in December 2019 in Wuhan, China was ultimately found to be caused by a new virus, the "2019 novel Coronavirus" (2019-nCoV) or SARS-CoV-2 formally named by the World Committee on Virus Classification, [1][2][3] and the disease caused by this virus was named as COVID-19 by the World Health Organization. 4 , 5 This virus has a characteristic crown representing the spike peplomers on the viral envelope, with strong infectivity and general suscepti-bility to people of all ages and across the globe.…”
Section: Introductionmentioning
confidence: 99%